2006
DOI: 10.1207/s15548430jlr3801_3
|View full text |Cite
|
Sign up to set email alerts
|

Power through Voicing Others: Girls' Positioning of Boys in Literature Circle Discussions

Abstract: This qualitative study uses an analysis of literature circle discussions to illuminate larger issues of gender and social class for a group of fifth-grade students. By examining how four students were positioned and positioned themselves within these literature conversations, I demonstrate that the roles reproduced certain gender-and class-specific storylines. These storylines served to empower the girls' literacy development, while simultaneously disempowering the literacy development of the boys. I draw upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…The literature circle provide a basis for student-centered studies, significantly affects the level of participation in classes and brings learning experiences by applying (Clarke, 2006;Cazden, 2001;Nystrand, Gamoran, & Heck, 1993;Rosenblatt, 1978). The literature circle method is a remarkable tool for students to be interested in texts (Deniz & Ersoy, 2016;Stien & Beed, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The literature circle provide a basis for student-centered studies, significantly affects the level of participation in classes and brings learning experiences by applying (Clarke, 2006;Cazden, 2001;Nystrand, Gamoran, & Heck, 1993;Rosenblatt, 1978). The literature circle method is a remarkable tool for students to be interested in texts (Deniz & Ersoy, 2016;Stien & Beed, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Teachers also face what Janks (2004Janks ( , 2009) refers to as the tension of balancing dominant and diverse forms of literacy-the access paradox-valuing diverse forms of literacy while, at the same time, supporting students' mastery of dominant forms of literacy needed to succeed in high-stakes testing environments. Within critical pedagogy, students are provided opportunities to study social constructs like gender (e.g., Clarke, 2009), race (e.g., Rogers & Mosley, 2006), powerful texts (e.g., Gutiérrez, 2008Gutiérrez, /2011, and language ideologies (e.g., Martínez, 2010). Within critical pedagogy, students are provided opportunities to study social constructs like gender (e.g., Clarke, 2009), race (e.g., Rogers & Mosley, 2006), powerful texts (e.g., Gutiérrez, 2008Gutiérrez, /2011, and language ideologies (e.g., Martínez, 2010).…”
Section: Critical Literacy/critical Pedagogymentioning
confidence: 99%
“…Some scholars advise that literature circles be entirely student run, assuming that without adult interference, students will have more academic freedom and personal agency to respond (e.g., Daniels, 2002). Others suggest that no literature circle is devoid of power hierarchies and that excluding teachers by no means guarantees that students will speak freely (Clarke, 2006). In the current study, teacher and researcher participation in the literature circle encouraged students' exploration of interpretations but did not overtly challenge their perspectives.…”
Section: Rethinking Literature Circle Pedagogymentioning
confidence: 99%
“…Despite the enthusiasm for literature circles, scholarship has highlighted some of their complex and thorny aspects by considering how readers' responses to texts are driven by and located within a host of social practices. For instance, several studies have found that literature circles are intensely power-laden spaces in which students position one another socially in terms of ability level (Allen, Möller, & Stroup, 2003) and gender (Clarke, 2006;Evans, 1996). Other studies established that literature circle discussions sometimes reinforce stereotypes rather than engage students in democratic practices (Alvermann, 1995;Orellana, 1995), calling into question egalitarian assumptions about this instructional approach.…”
mentioning
confidence: 99%